The Relationship Between Acupressure Therapy And Reducing Menstrual Pain Intensity (Dysmenorrhea) In Adolescent Females At SMA Paba Binjai In 2024 - Rismeni Saragih (International Journal of Health and Social Behavior, 2025)
Dysmenorrhea is a disorder characterized by lower abdominal pain that occurs during menstruation. Dysmenorrhea problems in adolescent girls if not treated immediately can have a negative impact on adolescent productivity including learning activities. There are several ways that can be done to reduce menstrual pain (dysmenorrhea). However, this study only carried out Acupressure Therapy to reduce dysmenorrhea to determine whether there was a relationship between acupressure and reducing the intensity of menstrual pain (dysmenorrhea) in adolescent girls at SMA PABA Binjai in 2024. The research method used the Chi-Square test. With the population and sample of this study were adolescent girls with menstrual pain (dysmenorrhea) in grades X & XI SMA PABA Binjai in 2024 as many as 28 respondents using the total sampling technique. The research instrument used a procedure and observation sheet. The data used are primary and secondary data. Data analysis univariate and bivariate using the Chi-Square test. The results of the study indicate that there is a Relationship between Acupressure Therapy and Reducing the Intensity of Menstrual Pain (Dysmenorrhea) in Adolescent Girls at SMA PABA Binjai in 2024 with a degree of significance (α) = 0.05 and df = 1, the calculation results are Sig (2-tailed) 0.000 <(α) = 0.05, then Ho is rejected and Ha is accepted. The conclusion is that there is a relationship between acupressure therapy and reducing the intensity of menstrual pain (dysmenorrhea). It is hoped that adolescent girls with menstrual pain (dysmenorrhea) will routinely carry out acupressure therapy according to the technique to reduce menstrual pain (dysmenorrhea) felt during menstruation.